CORRELATION BETWEEN READING ATTITUDE AND READING COMPETENCE OF GRADE 4 PUPILS - Luis, Joshua (SEAMEO QITEP in Language, 2024)
Reading is a fundamental skill essential for academic success and lifelong learning. It serves as the foundation for acquiring knowledge, developing critical thinking, and fostering creativity. Despite its importance, many learners face challenges in developing strong reading skills, often influenced by various factors such as reading attitudes. Understanding these factors is crucial for designing effective interventions that enhance literacy outcomes. This study explored the relationship between reading attitude and reading competence among Grade 4 learners. Utilizing a descriptive-correlational design, the research examined how pupils’ reading attitude correlates with their reading competence. A total of 60 Grade 4 pupils were surveyed, and their reading competence and reading attitude were evaluated through standardized tools— Phil-IRI (Philippine Informal Reading Inventory) and ERAS (Elementary Reading Attitude Survey). The findings revealed a moderate positive correlation (r = 0.48) with a computed p-value of <.01 between reading attitude and reading competence, highlighting the importance of fostering a positive attitude to improve literacy skills. The study advocates for a comprehensive reading program that nurtures positive attitudes toward reading to enhance both reading competence and learning outcomes.